Emerging Thrombotic Disorders Associated with Virus-Based Innovative Therapies: From VITT to AAV Gene Therapy–Related Thrombotic Microangiopathy - Benemei, Silvia; Gatto, Francesca; Marcucci, Rossella; Gresele, Paolo (Thrombosis and Haemostasis, 2024)
Gene therapy is a promising therapeutic approach for treating life-threatening disorders. Despite the clinical improvements observed with gene therapy, immune responses either innate or adaptive against the vector used for gene delivery, can affect treatment efficacy and lead to adverse reactions. Thrombotic microangiopathy (TMA) is a thrombosis with thrombocytopenia syndrome (TTS) characterized by microangiopathic hemolytic anemia, thrombocytopenia, and small vessel occlusion known to be elicited by several drugs, that has been recently reported as an adverse event of adeno-associated virus (AAV)-based gene therapy. TMA encompasses a heterogenous group of disorders, its classification and underlining mechanisms are still uncertain, and still lacks validated biomarkers. The identification of predictors of TMA, such as vector dose and patient characteristics, is a pressing need to recognize patients at risk before and after AAV-based gene therapy administration. This review aims to explore the literature on TMA associated with AAV-based gene therapy in the larger context of TMA (i.e., hemolytic-uremic syndrome, thrombotic thrombocytopenic purpura, and other drug-related TMAs). Considering the wide attention recently gained by another TTS associated with a non-gene therapy viral platform (adenovirus, AV COVID-19 vaccine), namely vaccine-induced immune thrombocytopenia and thrombosis (VITT), AAV gene therapy–related TMA mechanisms will be discussed and differentiated from those of VITT to avoid recency bias and favor a correct positioning of these two recently emerged syndromes within the heterogenous group of drug-related TTS. Finally, the review will discuss strategies for enhancing the safety and optimize the management of AAV-based gene therapy that is emerging as an efficacious therapeutic option for disparate, severe, and often orphan conditions.
Keywords: adeno-associated virus (AAV); biomarkers; gene therapy; thrombotic microangiopathy (TMA); vaccine-induced immune thrombocytopenia and thrombosis (VITT)